IL-15 Enhances Activation and IGF-1 Production of Dendritic Epidermal T Cells to Promote Wound Healing in Diabetic Mice - Wang, Yangping; Bai, Yang; Li, Yashu; Liang, Guangping; Jiang, Yufeng; Liu, Zhongyang; Liu, Meixi; Hao, Jianlei; Zhang, Xiaorong; Hu, Xiaohong; Chen, Jian; Wang, Rupeng; et al. (Frontiers in Immunology, 2017)
Altered homeostasis and dysfunction of dendritic epidermal T cells (DETCs) contribute to abnormal diabetic wound healing. IL-15 plays important roles in survival and activation of T lymphocytes. Recently, reduction of epidermal IL-15 has been reported as an important mechanism for abnormal DETC homeostasis in STZ-induced diabetic animals. However, the role of IL-15 in impaired diabetic wound healing remains unknown. Here, we found that, through rescuing the insufficient activation of DETCs, IL-15 increased IGF-1 production by DETCs and thereby promoted diabetic skin wound repair. Regulation of IGF-1 in DETCs by IL-15 was partly dependent on the mTOR pathway. In addition, expression of IL-15 and IGF-1 were positively correlated in wounded epidermis. Together, our data indicated that IL-15 enhanced IGF-1 production by DETCs to promoting diabetic wound repair, suggesting IL-15 as a potential therapeutic agent for managing diabetic wound healing.